Parking Space Performance Evaluation In General Hospital City Ibnu Sina Gresik - Hadi Prasetya; Sri Wiwoho Mudjanarko (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
Parking is one element means that can not be separated from road transport system as a whole. Parking is a problem that is often encountered in the urban transport system both in major cities and in the growing city. Parking problems are also a thing that can not be handled several hospitals. The number of hospital facilities will encourage people to visit the hospital. The purpose of this study was to analyze the needs of a parking space, to determine the pattern of the corresponding parking space is used in a general hospital Avicenna. The method applied in this research is to conduct a survey directly in the field include admission-out to get the data of the vehicle. Analysis of vehicle data to get a parking volume, accumulation, The results of the analysis obtained by the characteristics of parking for 2-wheel vehicles and wheels 4 have the highest volume in a row parking for 679 vehicles and 120 vehicles